The Treaty of Hudaibiyah: The First Concept of Preventive Diplomacy leading to the Achievement of Peace - Kazem, Tarek (Український політико-правовий дискурс, 2026)
The Treaty of Hudaibiyah stands out as one of the most prominent of the historical junctures in Islamic history, redefining the concept of victory and establishing the principle that a calm, balanced decision can achieve what protracted battles cannot. This treaty represented a unique model of crisis management, demonstrating the capability of the leadership to transform apparent challenges into major strategic opportunities. The Treaty of Hudaibiyah was concluded in the sixth year of the Hijra between the Muslims, and the Quraysh. This occurred after the Muslims departed Medina for Mecca to perform Umrah, with no intention of fighting or confrontation. Although the treaty appeared on the surface to be an agreement involving temporary concessions, it constituted, in essence, a profound strategic gain. The ultimate goal of the Hudaibiyah treaty or any treaty should contribute to ending bloodshed and establishing peace. The Treaty established a new era of political and social stability, reshaping balance of power in the Arabian Peninsula. In the history of diplomacy, the Treaty of Hudaibiyah stands out as an exceptional example of what we call today "realpolitik". It is the most vivid lesson of transforming "tactical concessions" into major "strategic victories". The Treaty teaches us that true victory often relies on strategy, resilience, and wisdom rather than brute force. The Muslims’ adherence to the covenants, despite their apparent severity, paved the way for the great conquest. The main objective of the article is to show how the Treaty of Hudaibiyah directly aligns with the concept of Preventive Diplomacy through the following key dimensions: De-escalation of Conflict, Crisis Management and Direct Dialogue, Confidence-Building Measures and Flexibility for Strategic Gains. The novelty of the research lies in highlighting the legal aspect of the "Hudaibiyahcase" as a historical fact of the successful application of the preventive diplomacy tools leading to the achievement of peace.